Closely spaced tri‐band frequency selective surfaces based on split ring slots. Issue 9 (1st April 2016) - Fabian‐Gongora, H.; Martynyuk, A.E.; Rodriguez‐Cuevas, J.; Martinez‐Lopez, J.I.
Abstract : A tri‐band frequency selective surface (FSS) with close band spacing based on split ring slots for y ‐polarised incident waves is investigated. The close band response is obtained by reducing the strong mutual coupling between the closely packed concentric rings through splitting the ring slots and redistributing the location of the surface currents at resonances. To validate the proposed FSS, a Ka band FSS was designed, fabricated and tested. Experimental results showed closely spaced resonances at 27.3, 31.7 and 36.2 GHz. Frequency ratios of 1.16 for the second to the first resonance, and 1.14 for the third to the second one were obtained. Also, good stability is observed for oblique incidence.